2014
DOI: 10.1038/cddis.2014.196
|View full text |Cite
|
Sign up to set email alerts
|

FoxO mediates APP-induced AICD-dependent cell death

Abstract: The amyloid precursor protein (APP) is a broadly expressed transmembrane protein that has a significant role in the pathogenesis of Alzheimer's disease (AD). APP can be cleaved at multiple sites to generate a series of fragments including the amyloid β (Aβ) peptides and APP intracellular domain (AICD). Although Aβ peptides have been proposed to be the main cause of AD pathogenesis, the role of AICD has been underappreciated. Here we report that APP induces AICD-dependent cell death in Drosophila neuronal and n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
56
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(66 citation statements)
references
References 53 publications
6
56
1
Order By: Relevance
“…The other cleavage products created by α- and β-cleavage, CTF83 and CTF99, respectively, do not have well defined roles. However, γ-secretase cleavage of the CTFs results in the release of the APP Intracellular Domain (AICD), which binds Fe65 and TIP60 for potential transcriptional activation of downstream targets (Cao and Sudhof, 2001), ultimately promoting cell death and impairing neurogenesis (Ghosal et al, 2010; Wang et al, 2014). The final and most-studied products of APP cleavage are the Aβ species, predominantly Aβ 40 and some Aβ 42 .…”
Section: App Processing and The Endosomementioning
confidence: 99%
“…The other cleavage products created by α- and β-cleavage, CTF83 and CTF99, respectively, do not have well defined roles. However, γ-secretase cleavage of the CTFs results in the release of the APP Intracellular Domain (AICD), which binds Fe65 and TIP60 for potential transcriptional activation of downstream targets (Cao and Sudhof, 2001), ultimately promoting cell death and impairing neurogenesis (Ghosal et al, 2010; Wang et al, 2014). The final and most-studied products of APP cleavage are the Aβ species, predominantly Aβ 40 and some Aβ 42 .…”
Section: App Processing and The Endosomementioning
confidence: 99%
“…Very recently, FOXO has also been implicated in drug-mediated cytoskeletal stress because of its effects on neuronal mt organization following pharmacological damage, which requires Akt kinase [19, 20]. Importantly, some FOXO transcription factors also influence the PTX-induced inhibition of the androgen receptor (AR), suggesting a connection between the mt-dependent trafficking of the AR and the clinical efficacy of PTX as well as that of other taxanes [21].…”
Section: Introductionmentioning
confidence: 99%
“…Although Foxo3 has not been identified as an upstream regulator of APP processing, a recent study identified Foxo3 as a downstream target of APP, which induces APP intracellular domain (AICD)-induced death in neuronal and non-neuronal tissues (Wang et al, 2014). Glutamate treatment led to an ∼2-fold increase in APP promoter activity in 12 h, which gradually increased to 2.5-fold by 24 h (Fig.…”
Section: Activation Of Foxo3 Is Neurotoxic In Glutamate-treated Cellsmentioning
confidence: 99%